Ethical practice and Human Resource performance in Nairobi City County government, Kenya (African Journal of Science, Technology and Social Sciences, 2024)
This study aimed to examine the relationship between  ethical practice and human resource performance in Nairobi City County Government, Kenya.The study was built on  Stakeholder Theory.The study's target population comprised 46 employees, including  principal human resource officers, administrative officers, and human resource officers, based at City Hall, Nairobi. Data was collected through a semi-structured questionnaire. Data analysis was done using SPSS software, and key findings revealed that the county government’s  application of accountability  and ethical conduct positively impacts human resource performance. A positive correlation coefficient of 0.582 indicates a significant and positive linear relationship between ethical practices and human resource performance. Ethical guidelines and policies play a vital role in shaping the ethical culture within county governments and enhancing employee morale and job satisfaction.Ethical conduct should thus be at the forefront of the county government’s operations.The study roots for increased emphasis on competency-based hiring practices.
Keywords: Ethical Practices; Competency Based hiring; Stakeholder theory